2016
DOI: 10.1182/blood-2015-11-683052
|View full text |Cite
|
Sign up to set email alerts
|

Redundant and nonredundant roles for Cdc42 and Rac1 in lymphomas developed in NPM-ALK transgenic mice

Abstract: Key Points Rac1 and Cdc42 possess nonredundant roles in preventing apoptosis of NPM-ALK lymphoma cells. Simultaneous deletions of both Rac1 and Cdc42 prevents NPM-ALK lymphoma dissemination in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…32,48 More broadly, these findings suggest the importance of TCR signaling as a key pathway involved in lymphomagenesis, 60 as has been demonstrated in mice 61 and is evidenced further by other genes altered by various mechanisms in PTCLs, including rearrangements of SYK, copy number gains of ITK, and point mutations of FYN. 16,49,57,62 These potentially targetable molecular alterations show promise for advances analogous to those resulting from elucidation of dysregulated B-cell receptor signaling in B-cell NHLs.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…32,48 More broadly, these findings suggest the importance of TCR signaling as a key pathway involved in lymphomagenesis, 60 as has been demonstrated in mice 61 and is evidenced further by other genes altered by various mechanisms in PTCLs, including rearrangements of SYK, copy number gains of ITK, and point mutations of FYN. 16,49,57,62 These potentially targetable molecular alterations show promise for advances analogous to those resulting from elucidation of dysregulated B-cell receptor signaling in B-cell NHLs.…”
Section: Discussionmentioning
confidence: 53%
“…Because VAV1 GEF activity predominantly targets the Rho family GTPase RAC1 (and to a lesser extent RHOA and CDC42), 30,31 and RAC1 has been demonstrated to promote migration in an ALCL model, 32 we measured Rac activation following VAV1-GSS transfection in Jurkat cells. VAV1-GSS overexpression increased active Rac (GTP-Rac; 173% of control; P 5 .054; Figure 4A-B).…”
Section: Vav1-gss Drives Growth Through Rac1 and Can Be Targeted By Rmentioning
confidence: 99%
“…Early studies showed that treatment with NSC23766, a chemical inhibitor of Rac1, blocked the invasion and metastasis phenotype in multiple cancer cells 42 . It has also been shown that inhibition of Rac1 signaling in a murine lymphoma model abrogated tumor progression and metastasis in vivo 43 . This evidence demonstrated that Rac1 could be regarded as a therapeutic target for anticancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ALK fusion-mediated activation of STAT3 has been shown to be required for the maintenance of the transformed phenotype in ALK + ALCL (Chiarle et al 2005). ALK fusions constitutively activate VAV1 and VAV3 in ALCL, increasing RAC1 and CDC42 activity, down-regulating the Wiskott-Aldrich syndrome protein (WASP) and WASP-interacting protein (WIP) tumor suppressors and promoting lymphoma survival (Choudhari et al 2016;Menotti et al 2019).…”
Section: Anaplastic Large-cell Lymphomasmentioning
confidence: 99%